Low Levels of PSMA Expression Limit the Utility of (18)F-DCFPyL PET/CT for Imaging Urothelial Carcinoma - Campbell, Scott P. (Ann Nucl Med, 2017)
OBJECTIVE: To explore the clinical utility of PSMA-targeted (18)F-DCFPyL PET/CT in patients with metastatic urothelial carcinoma. METHODS: Three patients with metastatic urothelial were imaged with (18)F-DCFPyL PET/CT. All lesions with perceptible radiotracer uptake above background were considered positive. Maximum standardized uptake values were recorded for each detected lesion and findings on (18)F-DCFPyL PET/CT were compared to those on conventional imaging studies. To further explore PSMA as a molecular target of urothelial carcinoma, RNA-sequencing data from The Cancer Genome Atlas was used to compare the relative expression of PSMA among cases of bladder cancer, prostate cancer, and clear cell renal cell carcinoma. Additionally, immunohistochemical staining for PSMA expression was performed on a biopsy specimen from one of the imaged patients. RESULTS: (18)F-DCFPyL PET/CT allowed for the detection of sites of urothelial carcinoma, albeit with low levels of radiotracer uptake. Analysis of RNA-sequencing data revealed that bladder cancer had significantly lower levels of PSMA expression than both prostate cancer and clear cell renal cell carcinoma. Consistent with this observation, immunohistochemical staining of tissue from one of the imaged patients demonstrated a low level of neovascularization and nearly absent PSMA expression. CONCLUSION: The relatively scant expression of PSMA by urothelial cancer likely limits the utility of PSMA-targeted PET imaging of this malignancy. Future research efforts should focus on the development of other molecularly targeted imaging agents for urothelial carcinoma.